Femtosecond Laser Combined with Hydrothermal Method to Construct Three-Dimensional Spatially Distributed Wurtzite ZnO Micro/Nanostructures to Enhance Photocatalytic Properties - He, Yaowen (Langmuir : the ACS journal of surfaces and colloids, 2024)
Conventional approaches employing nanopowder particles or deposition photocatalytic nanofilm materials encounter challenges such as performance instability, susceptibility to detachment, and recycling complications in practical photocatalytic scenarios. In this study, a novel fabrication strategy is proposed that uses femtosecond laser direct writing of self-sourced metal to prepare a self-supporting microstructure substrate and combines the hydrothermal method to construct a three-dimensional spatially distributed metal oxide micro/nanostructure. The obtained wurtzite ZnO micro/nanostructure has excellent wetting properties while obtaining a larger specific surface area and can achieve effective adsorption of methyl orange molecules. Moreover, the tight integration of ZnO with the surface interface of the self-sourced metal microstructure substrate will facilitate efficient charge transfer. Simultaneously, it improves the efficiency of light utilization (absorption) and the number of active sites in the photocatalytic process, ultimately leading to excellent photodegradation stability. This result provides an innovative technology solution for achieving efficient semiconductor surface-interface photocatalytic performance and stability